Cultural Differences in Careless Responding. (April 2019) - Grau, Ina; Ebbeler, Christine; Banse, Rainer
Careless responding (CR) in surveys has been identified as a serious threat for the validity of survey data. It occurs when participants respond without following the instructions or reading the content of items. The purpose of this article is to assess and explain the amount of CR at the individual and country level. In our study, individual CR (measured by indices using a short Big 5 personality questionnaire) correlated with education level and personality traits. In addition, using a sample of 8, 320 participants from 34 countries, CR at the country level was investigated and it was strongly correlated with the cultural dimensions: human development, individualism, gender inequality, and power distance. CR can be seen as a powerful predictor of differences between countries. Finally, a comparison between CR and response styles (extreme and midpoint answers, acquiescence, and socially desirable responses) was conducted. CR and response styles showed some overlap, but loaded on different factors. CR is compatible with extreme answers, midpoint answers, and acquiescence, but different from social desirability. Social desirability is the only response style which requires careful reading of items.